Abatacept (cytotoxic T lymphocyte antigen 4-immunoglobulin) improves B cell function and regulatory T cell inhibitory capacity in rheumatoid arthritis patients non-responding to anti-tumour necrosis factor-α agents. (24th July 2014) - Picchianti Diamanti, A; Rosado, M M; Scarsella, M; Germano, V; Giorda, E; Cascioli, S; Laganà, B; D'Amelio, R; Carsetti, R
Summary: The use of biological agents combined with methotrexate (MTX) in rheumatoid arthritis (RA) patients has strongly improved disease outcome. In this study, the effects of abatacept on the size and function of circulating B and T cells in RA patients not responding to anti-tumour necrosis factor (TNF)-α have been analysed, with the aim of identifying immunological parameters helpful to choosing suitable tailored therapies. We analysed the frequency of peripheral B and T cell subsets, B cell function and T regulatory cell (Treg ) inhibitory function in 20 moderate/severe RA patients, according to the European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) criteria, primary non-responders to one TNF-α blocking agent, who received abatacept + MTX. Patients were studied before and 6 months after therapy. We found that abatacept therapy significantly reduced disease activity score on 44 joints (DAS)/erythrocyte sedimentation rate (ESR) values without causing severe side effects. The size of the circulating B and T cell compartments in RA patients was not significantly different from healthy donors, but B cell proliferation and plasma cell differentiation was impaired before therapy and restored by abatacept. While Treg cell frequency was normal, its inhibitory function was absent before therapy and was partially recovered 6 months after abatacept. B and Treg cell function is impaired in RA patients not responding to the first anti-TNF-α agent. Abatacept therapy was able to rescue immune function and led to an effective and safe clinical outcome, suggesting that RA patients, in whom anti-TNF-α failed, are immunologically prone to benefit from an agent targeting a different pathway.